System for performance assessment of solar home systems - Pinto Calderón, María de los Ángeles; Muñoz Maldonado, Yecid Alfonso; Vera Suárez, Carlos Eduardo (Ingeniería Solidaria, 2021)
This article is the product of the investigation "Development of a photovoltaic pilot system for performance assessment of isolated systems in the Renewable Energy Laboratory at UNAB" developed at the Universidad Autónoma de Bucaramanga (UNAB) in 2019, considering off-grid solar home systems (SHS) are a feasible alternative in rural remote areas, where access to electric power is limited due to their power grid lack. The objective is to develop a PV test system for off-grid solar home system (SHS) performance assessment. For the development, a case study is analyzed based on the behavior of a user's daily demand in Hato Corozal, Casanare. Design aspects of the system are also elaborated. Key performance parameters identified to be monitored are solar irradiance, power generation, energy consumption and battery charge status. Two scenarios of daily demand behavior are analyzed to evaluate the influence of load shifting on the performance of the system. The applied design criteria were validated obtaining that the sized system satisfied the energy requirement without a battery’s depth of discharge (DOD) deeper than specified, showing the capacity of the system to make studies in longer periods with the possibility of generating different demand behavior scenarios. The designed system presents a performance ratio of 0,77 when a daily consumption is considered, while when shifting loads to coincide them with the higher irradiance the PR was 0,95. In both cases, the SoC was higher than 79%, maintaining a DOD of the battery bank according to the specified in the sizing. The system presents excess energy that can be used by expanding the capacity of the battery bank. Findings suggest that a higher performance ratio is obtained when coinciding consumption peaks with the hours of higher solar radiation.
Keywords: off-grid; performance; photovoltaic; rural; solar home system